(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2017)
This study aims to highlight the role of financial control in the development of government performance through the use of "GFS" system and its application in the service of government units, which will help them in how to use financial resources efficiently through the quality of accounting information provided by this system in the financial statements that reflect the predictability in that fiscal policy of the state through government programs and activities fee as well as to identify weaknesses and address them quickly in order to avoid wastage and loss of public money, which leads to the possibility of utilization of available financial resources of the state to effectively and efficiently, has been reached that the failure of government accounting system applied in terms of outputs which do not meet the needs of government reports and financial statements for users over the use of available resources in the economic development and processing of financial and administrative corruption and to reflect on the proper use of available resources. Although "GFS" system applied in full is an important financial tool of public financial management in hand toward the optimal use of available resources and about the implementation of government programs and activities that support economic development through improved financial performance by providing useful information that will help in pursuing government unit operations has therefore It recommended that researchers in need "GFS" system applied fully to the development of accounting and audit work environment through the replacement of financial reports and records prepared offline reports and records of accounting other fit with the "GFS" system, which is more reflective and clearer financial position and financial performance of the unit by providing more information relevant and useful to meet as much as possible the needs of different users of information and private auditors to track unity government operations and evaluate its financial performance.